LEGAL ISSUES RELATED TO DATA PROTECTION AND PRIVACY RIGHT IN CYBERSPACE (International Journal of Food and Nutritional Sciences, 2021)
The rapid advancement of technology and the increasing reliance on digital platforms have significantly transformed how we interact, communicate, and conduct business. While these advancements offer numerous benefits, they also present complex legal challenges related to data protection and privacy rights. As our personal information increasingly migrates to the digital realm, safeguarding these rights becomes paramount. This article delves into the key legal issues surrounding data protection and privacy in cyberspace. The concept of data privacy is not new, but its significance has amplified in the digital age. Traditionally, privacy concerns were primarily associated with physical spaces and offline interactions. However, with the advent of the internet, the boundaries of privacy have blurred. Our online activities generate vast amounts of personal data, from browsing history and social media posts to financial transactions and health records. This data is collected, stored, and processed by a multitude of entities, including businesses, governments, and cybercriminals. The internet has become an indispensable tool for individuals and organizations alike. From social media platforms to online shopping websites, our digital footprints are constantly being tracked and analyzed. While data collection enables personalized experiences and targeted advertising, it also raises concerns about privacy and security.